Students’ Perception towards Master of Business Studies (MBS) Semester System: A Case Study of Nepal Commerce Campus (Pravaha, 2018)
The study sought to understand and analyze students’ perception towards MBS semester system taking a case of Nepal Commerce Campus with regard to (a) academic resources, (b) course organization and planning, (c) physical resources, (d) governance and image, and (e) overall perception of students. It followed descriptive research design with using questionnaire survey instrument. The population of this study comprised all 668 MBS semester students and the sample consisted 246 students selected through random sampling techniques. The survey questionnaire was set in seven sections with 30 questions of various types to collect data. Collected data were analyzed with the help of SPSS software (version 23). The research result revealed that the perception of the students towards all aspects is quite satisfactory except toilets and canteen facilities of Nepal Commerce Campus. The study drew some feedback and suggestions from students for the betterment of the college. It covered those students who were studying MBS semester system since the last five out of 48 month’s course cycle therefore it didn’t cover the aspects of semester system. It enhances the understanding of stakeholders about the issues of semester system at master’s level.Pravaha Vol. 24, No. 1, 2018, Page: 181-195